Podstawy i elementy formacji chrześcijańskiej według Leona Wielkiego - Ziółkowska, Marta (Vox Patrum, 2013)
The pontificate of Leo the Great (440-461) was one of the longest in the history of the Church. Since his days as Pope were difficult and complicated, Leo’s part in the civil and political events of the Roman Empire was significant. That time was also characterized by continuous christological debates and controversies in which Leo’s voice as that of the head of the Catholic Church was decisive. He considered it his fundamental duty to strengthen Christian faith through formation and spiritual direction of the faithful. It also involved the formation of Christian character. His Sermons clearly testify to St. Leo’s fundamental role as a spiritual guide who strives for the salvation of the souls of those who are called to perceive their earthly lives in the proper manner. This paper offers a detailed analysis of Sermons delivered on various occasions, including Advent, Lent or Ember days which were for Pope Leo an occasion for a systematic exercise of his responsibilities. The first part of the paper deals with Leo’s conception of the basis and goals of spiritual formation in the 5th c. The second part sets forth the main elements of the formation programme. Consequently, the ancient concept of Christian formation has been presented here with its practical adaptations as implemented in daily striving for holiness.